Magnitude of Anemia and Its Associated Factors among Pregnant Women Attending Antenatal Care at Najo General Hospital, Northwest Ethiopia - Wakshuma Gari; Arega Tsegaye; Tsige Ketema (Anemia)
Anemia is one of the major causes of morbidity for pregnant women in resource-limited regions. Yet robust research-based evidence on this vital public health problem in remote areas where the problem could be massive is quite limited in Ethiopia, one of the developing countries. Thus, this study is aimed to assess the magnitude of anemia and its associated risk factors among pregnant women attending one of the health facilities in Ethiopia. A facility-based cross-sectional study design was employed in 2019. A total of 384 pregnant women attending the antenatal care (ANC) unit of Najo General Hospital, Northwest Ethiopia, were included in the study. Their sociodemographic characteristics, and medical, obstetric, and gynecological history were collected using pretested interview questionnaires. Blood samples were collected from each participant for the determination of malaria parasite and hemoglobin (Hb) level. In addition, stool samples were collected for examination of intestinal parasites. Data were analyzed using Statistical Package for Social Science (SPSS) software version 25. The overall magnitude of anemia among pregnant women was 37.8% (95% CI, 32.8%–42.3%). The proportion of mild anemia, moderate anemia, and severe anemia was 24%, 11%, and 2.3%, respectively. Some variables such as absence of malaria infection (AOR: 0.195, 95% CI: 0.066–0.576), lack of history of abortion (AOR: 0.469, 95% CI: 0.265–0.830), and absence of history of anemia (AOR: 0.227, 95% CI: 0.134–0.385) were identified as protective variables of anemia during pregnancy, while urban residence (AOR: 1.753, 95% CI: 1.013–3.034) was unexpectedly found as a predisposing factor. Despite the higher number of anemic pregnant women observed in the current study, pregnancy-associated anemia is moderate public health importance in the study area.